Diplomasi Indonesia Terhadap UNESCO Dalam Meresmikan Noken Sebagai Warisan Budaya Indonesia Tahun 2012 - Gloria, Nuvola; Harto, Syafri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research explains about Indonesian Diplomacy for UNESCO Paten’s Noken. It has already been fact to be forced by every nation and state. Multi-track Diplomacy.Used to Foster Peace between States or Particular interest. Its authenticity on the fact that it relies on various contributions from government and non government institutions. This Article will explain how the multi-track diplomacy work to help the Indonesian Government’s push UNESCO to get paten Indonesia’s Noken.Keywords: Soft Diplomacy, Multi Track Diplomacy, Noken, Cultural Heritage and UNESCO